Hidden Politics behind the Gen-Z Movement (2025, September) in Nepal - Timalsina, Saroj Kumar; Shrestha , Suman Kumar (Educational Journal, 2025)
The September 2025 large-scale youth uprising in Nepal is often referred to as the "Gen-Z protests." The uprising began when the government shut down most social media sites, but it soon expanded beyond its original purpose to reflect broader complaints that had been simmering among younger people. Widespread corruption in political institutions, the public display of privilege enjoyed by wealthy families, now known as "nepo kids," high rates of youth unemployment, and government restrictions on online freedoms that had become linked to generations and upward mobility were among the many issues that caused public outrage. These criticisms, though well-known and powerfully framed, were only the beginning of a more complex political endeavor. Below them was a system of clandestine politics that shaped the direction and outcome of the movement. These included conflicts over control of cyber narratives and information systems; institutional weaknesses that permitted temporary constitutional or legal wrangling; pressures from Nepal's geopolitical context; and calculated actions by political elites to delegitimize, scapegoat, or co-opt opposition. Since caste, class, gender, and geography all had an impact on who joined and whose concerns were given priority, the unequal patterns of participation within the movement itself were equally significant. This article examines these hidden political dynamics and situates them within a larger comparative framework of youth mobilizations in South Asia to ascertain whether the Gen-Z protests will persist as intermittent disruptions or evolve into more lasting and transformative forms of democratic participation.